Ehealth monitoring in irritable bowel syndrome patients treated with low fermentable oligo-, di-, mono-saccharides and polyols diet - Pedersen, Natalia (Baishideng Publishing Group Inc, 2014)
In the present study we report on changes in irritable bowel syndrome-severity scoring system (IBS-SSS) and irritable bowel syndrome-quality of life (IBS-QoL) in 19 IBS patients, aged 18 to 74 years (F/M: 14/5), during 12 wk registering their symptoms on the web-application (www.ibs.constant-care.dk). During a control period of the first 6-wk patients were asked to register their IBS-SSS and IBS-QoL on the web-application weekly without receiving any intervention. Thereafter, low fermentable oligo-, di-, mono-saccharides and polyols (FODMAP) diet (LFD) was introduced for the next 6 wk while continuing the registration. Though a small sample size a significant improvement in disease activity (IBS-SSS) was observed during both the control period, median: 278 (range: 122-377), P = 0.02, and subsequently during the LFD period, median: 151 (range: 29-334), P < 0.01. The IBS-QoL solely changed significantly during the LFD period, median: 67 (37-120), P < 0.01. The significant reduction in disease activity during the control period shows a positive effect of the web-application on IBS symptoms when presented as a “traffic light”. However adding the diet reduced IBS-SSS to < 150, inactive to mild symptoms. In the future results from larger scale trials are awaited.